异基因造血干细胞移植后出血性膀胱炎的临床特征及高危因素分析 (Zhonghua Xue Ye Xue Za Zhi, 2019)
OBJECTIVE: To explore the relative risk factors, clinical intervention and prognosis of hemorrhagic cystitis (HC) in patients with allogeneic hematopoietic stem cell transplantation (allo-HSCT). METHODS: From January 1 2010 to May 31 2017, 425 patients with allo-HSCT received a retrospective analysis. RESULTS: ①Among the 425 patients, 262 were male and 163 were female. The median age was 26 (2–56) years old. There were 138 cases of acute myeloid leukemia (AML), 96 cases of acute lymphoblastic leukemia (ALL), 29 cases of myelodysplastic syndrome (MDS), 98 cases of severe aplastic anemia (SAA) and 64 cases of chronic myeloid leukemia (CML). 221 cases of sibling match transplantation, 89 cases of unrelated donor transplantation and 115 cases of haplotype transplantation. ②108 patients (25.41%) developed HC, with the median time of onset of 32 (3–243) days and the median duration of 20 (3–93) days; 33 cases (30.56%) were grade Ⅰ, 49 cases of grade Ⅱ (45.36%), 21 cases (19.44%) of grade Ⅲ, and 5 cases (4.63%) of grade Ⅳ. ③103 cases of HC were cured, 5 patients were ineffective, 12 patients died and died of transplantation related complications (infection, recurrence, severe acute GVHD, secondary implant failure). ④Univariate analysis showed that age < 30, type of transplantation, CMV and acute GVHD were associated with the occurrence of HC after allo-HSCT. Multivariate analysis showed that acute GVHD was an independent risk factor for HC after allo-HSCT. CONCLUSION: Prognosis of HC after allo-HSCT was better after timely treatment.